Dynamics of Gender Law Towards Legal Protection for Women in Indonesia - Yudanto, Haryo; Permana, Yogi; Tristiani, Tristiani; Gunawan, Sigit; Yusup Permana, Deni (Asian Journal of Social and Humanities, 2024)
This study explores the dynamics of gender law that affect legal protection for women in Indonesia, especially in Cirebon City. Using a qualitative approach, data is analyzed from a variety of sources, including laws, policies, and legal practices. The results highlight challenges such as gender-based violence, discrimination, and limited access to health and education services. The proposed policy implications include harmonization of legislation, strengthening the role of the government and civil society, increasing gender awareness, and better legal protection for women.